Distributional effects of the European Emissions Trading System and the role of revenue recycling: Empirical evidence from combined industry- and household-level data - Johanna Cludius; Martin Beznoska; Viktor Steiner (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2012)
We calculate the expected distributional effects of the European Emissions Trading System combining industry and household-level data. By combining data on direct CO2 emissions by production sector from the German Environmental Account with the German Input-Output Accounts, we calculate the CO2 intensity of each sector covered by the EU ETS. We focus on the impact of price increases in the electricity sector, both directly in the form of higher electricity bills for consumers and indirectly through products that use electricity as an input to production. Distributional effects of price increases are analyzed on the basis of the German Income and Expenditure Survey for the year 2008 data and updated to 2013. We confirm the ex-ante expected regressive effect, which is, however, both rather small in magnitude and can be offset and even more than offset by revenue recycling, in particular the reduction of social security contributions on labour income.
Keywords: 330; Emissionshandel; EU-Europäisch; Energiepreis; Input-Output; Branche; Verteilungswirkung; Lohnsteuer; Sozialversicherungsbeitrag; Doppelte Dividende; Schätzung; Deutschland